SDG 2 – Zero Hunger : Food Security, Improved Nutrition and Sustainable Agriculture - Cheo, Ambe Emmanuel, author 646729; Tapiwa, Kugedera Andrew, author 646730; Emerald Publishing Limited (Online service) issuing body 646680 (Bingley, UK : Emerald Publishing Limited, 2021)
SDG2 links food security, nutrition and a sustainable but climate resilient agriculture. This multi-dimensional goal encompasses several specific targets and indicators, aimed at ending hunger, improving nutrition and achieving food security through sustainable and resilient agriculture and income increase.